2017
DOI: 10.1038/s41598-017-04382-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Dexmedetomidine Reduces the Requirement of Propofol during Total Intravenous Anaesthesia and Improves Analgesia after Surgery in Patients undergoing Open Thoracic Surgery

Abstract: The aim of this study was to assess the systemic and analgesic effects of epidural dexmedetomidine in thoracic epidural anaesthesia (TEA) combined with total intravenous anaesthesia during thoracic surgery. Seventy-one patients undergoing open thoracotomy were included in this study and randomly divided into three groups: Control group (Group C): patients received TEA with levobupivacaine alone and were intravenously infused with saline; Epidural group (Group E): patients received TEA with levobupivacaine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
3
9
0
1
Order By: Relevance
“…However, no further improvement was found in these two groups compared with the RD0.5 group. As described in a previous study and in our study, large doses of DEX have been shown to confer increased risk of sedation and bradycardia [ 33 ]. Therefore, side effects may be induced by increasing the dose of DEX.…”
Section: Discussionsupporting
confidence: 74%
“…However, no further improvement was found in these two groups compared with the RD0.5 group. As described in a previous study and in our study, large doses of DEX have been shown to confer increased risk of sedation and bradycardia [ 33 ]. Therefore, side effects may be induced by increasing the dose of DEX.…”
Section: Discussionsupporting
confidence: 74%
“…The lack of any symptoms or signs of neurological deficit reported by the new mothers suggested that epidural dexmedetomidine was safe when added to epidural morphine. The safety of epidural dexmedetomidine has been demonstrated in several previous studies (36,37).…”
Section: Discussionmentioning
confidence: 85%
“…Sufentanil has been used as local anesthetic adjuvant in epidural labor analgesia in a number of previous studies (1,12); therefore, sufentanil in combination with ropivacaine was used as the positive control in the present study. Dex has also been reported to display hemodynamic stability, pain alleviation, improved stress responses without respiratory depression when administered intravenously and intratracheally (19,20), and improved epidural and neuraxial blocks (21,22). Zhao et al (11) reported that compared with ropivacaine alone, the addition of Dex to epidural ropivacaine reduced the feeling of pain and did not result in motor blockage.…”
Section: Discussionmentioning
confidence: 99%